Effect and optimization of cutting speed and depth of cut in half-immersion up-milling of 6061 aluminium alloy / Nor Aznan Mohd Nor...[et al.] - Mohd Nor, Nor Aznan; Mohd Alisjabana, Syibli Syaddad; Seloraji, Ghirran; Tee, Yean Men; Teh, Jun Xian; Baharudin, B.T.H.T.; Arifin, M.K.M.; Leman, Z (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Cutting fluids are instrumental as manufacturing sectors achieved a variety of aims. As human rights and environmental protection have become a matter of global concern, end milling under dry conditions is becoming an important approach. However, cutting speed and depth of cut have different correlations on cutting temperature and surface roughness. Thus, end milling without using cutting fluids will result in catastrophes to cutting temperature, surface hardness, and surface roughness when cutting speed and depth of cut changes are not considered precisely. Consequently, optimising these two factors during end milling under dry conditions is an important aspect for manufacturing sectors. In this manuscript, 3² factorial experimental design were applied, whereas the significance of cutting speed and depth of cut, as well as their optimal combinations was analysed by analysis of variance (ANOVA) and desirability function analysis (DFA). The results indicated that cutting speed is the most significant factor on surface roughness, whereas depth of cut is the most dominant factor affecting cutting temperature and surface hardness. Furthermore, optimal combinations that minimise cutting temperature and surface roughness, and maximise surface hardness are obtained at the highest cutting speed and the lowest depth of cut.